Fabrication of a controllable anti-peeping device with a laminated structure of microlouver and polymer dispersed liquid crystals film. Issue 15 (8th December 2019) - Han, Cheng; Zhou, LE; Ma, Haipeng; Li, Chenyue; Zhang, Shuaifeng; Cao, Hui; Zhang, Lanying; Yang, Huai
ABSTRACT: Display devices with the narrow viewing angle (NVA) and the wide viewing angle (WVA) characteristics can simultaneously meet the demands for privacy protection and information sharing. Herein, we propose a novel method for fabricating a controllable anti-peeping device with a laminated structure of microlouver and polymer dispersed liquid crystals (PDLCs) film, and this device can be reversibly switched between a wider viewing angle range (VAR) for the WVA mode and a narrower viewing angle range (VAR) for the NVA mode at 0 V and 8 V, respectively. Also, the VARs of the controllable anti-peeping device can be dynamically tuned by varying dimensions of the microlouver structures and applying various voltages across the PDLCs film from 0 V to 8 V. The as-fabricated device provides display devices with controllable viewing angle characteristics, which can be applied in the display field with fascinating and practical functions. Graphical abstract: